Developing Early Children's Al-Quran Memorization Ability Through the Talaqqi Method - Syah, Milna Yanti; Asra, Muhammad; Nurhayati, Nurhayati; Faisal, Andi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze the development of Quran memorization skills in early childhood through the talaqqi method at TK IT Al Mawaddah Warrahmah Kolaka. Quran memorization at an early age plays a crucial role in instilling Islamic values and laying a child's religious foundation, but its implementation often faces challenges in the form of differences in children's concentration, memory, and learning readiness. This study uses a descriptive qualitative approach with a case study design. Data were obtained through observation, interviews with teachers, principals, and parents, as well as documentation of the memorization program. The results show that the application of the talaqqi method combined with systematic repetition (muroja'ah) can gradually improve children's memorization skills through teacher role models, daily habits, and ongoing mentoring. Supporting factors include a religious school environment, teacher competence, and parental involvement, while inhibiting factors include limited children's concentration, individual differences in abilities, and a lack of consistent mentoring at home. This study concludes that the talaqqi method makes a significant contribution to the development of Quran memorization skills in early childhood when applied consistently and collaboratively.